EFFECT OF GA3, ABA AND KINETIN ON THE RESPONSE OF THE HALOPHYTE ATRIPLEX HALIMUS TO SALINITY DURING GERMINATION - Soualem, Samira; Kouadria, Rabiaa; Labdelli, Amina; Adda, Ahmed (Plant Archives, 2018)
Atriplex halimus is a xerohalophytic perennial shrub native to the Mediterranean and has potential for use in ecological restoration programmes. In this study we investigate in order (i) the effects of increasing concentrations of NaCl (100, 200, 300, 400, 500 and 600mM) on germination of Atriplex halimus, (ii) the impact of phytohormones on the biochemical traits of germination, under 300 mM of NaCl. The increase in salinity resulted in the decrease of germination, water uptake and osmotic potential especially at high concentration. Germination in the ABA-treated group, was markedly decreased either in presence or absence of NaCl. However, both GA3 and kinetin were very effective in alleviating salt adverse effects. This was reflected in the increased content of soluble sugars, whereas ABA-treated seeds showed a contradictory effect under salinity. Consequently, a remarkable decrease in alpha amylase activity was observed under ABA and NaCl treatments, while no substantial changes were recorded after addition of kinetin in the absence of NaCl. Furthermore, in stressed seeds this activity was strongly reversed with GA3, Results suggest that these hormones appear regulate the germination under salinity, by aleviating the toxic effect of NaCl and contrubute to osmotic adjustment in this specie.
Keywords: Atriplex halimus; salt stress; germination; growth regulators; alpha amylase.